High genetic variability and polychromatism in Pachycoris torridus (Heteroptera: Scutelleridae) - Souza-Firmino, T. S. [UNESP]; Alevi, K. C. C. [UNESP]; Pereira, L. L. V. [UNESP]; Souza, E. R. S. [UNESP]; Junior, F. C. S. [UNESP]; Banho, C. A. [UNESP]; Carmo, G. O. [UNESP]; Itoyama, M. M. [UNESP] (Funpec-editora, 2015)
The stink bug Pachycoris torridus is listed among the most polyphagous insects in the world and it is a major pest of diverse crops, in particular the physic nut Jatropha curcas, which is used as a raw material for biodiesel production. A peculiar characteristic of this species is its high phenotypic variability, a characteristic that makes identification difficult: P. torridus has been described as a new species eight times. Thus, to aid in identification, genetic characterization of this insect was performed. We verified that, due to the high genetic variability of P. torridus, several genetic patterns exist that result in the same phenotype.
Keywords: Genetic variability; Stink bug; Molecular analysis